Thrill ride ebook - Walker, Julie Ann (Black Knights Inc., 2013)
A New York Times and USA Today Bestseller! "A first-rate thrill ride."—Publishers Weekly, Starred Review HE'S GONE ROGUE Ex-navy SEAL Rock Babineaux is as Cajun as they come—spicy, sexy, and more than a bit wicked. But would he actually betray his country? Even his best friends on the special-ops Black Knights team aren't sure they can trust him. Now the target of a massive manhunt, Rock knows the only way to protect the team—especially his partner, Vanessa—is to run... SHE WON'T BACK DOWN Rock might think he can outmaneuver them all, but he hasn't counted on how stubborn Vanessa Cordero can be. And she refuses to cut him loose. Sure, her partner has his secrets, but there's no one in the world she'd rather have by her side in a tight spot. Which is good because she and Rock are about to get very tight... Black Knights Inc. Series Hell on Wheels (Book 1) In Rides Trouble (Book 2) Rev It Up (Book 3) Thrill Ride (Book 4) Born Wild (Book 5) Hell for Leather (Book 6) Full Throttle (Book 7) Too Hard to Handle (Book 8) Wild Ride (Book 9 — coming April 2017!) Praise for Black Knights Inc. Series: "Julie Ann Walker is one of those authors to be put on a keeper shelf along with Nora Roberts, Suzanne Brockmann, and Allison Brennan."—Kirkus